Designing Website Promotion System On Sport Shoe Gallery Using Mecromedia Dreamweaver 8.0 - Dodi Hilamanda; Elly Agustina., J. SKom, MMSI (Jurnal Sistem Informasi, 2007)
The writing is about a quick profile of How to promote so the public can find completeinformation. Based on these circumstances, the authors make an application withreference to the running procedure, the application is expected to assist in overcomingany existing problems, to find out how to search for Sport Shoes Shop via the Internet.